Magnetic solid amine CO2 adsorbent as well as preparation method and application thereof

By preparing a magnetic porous nickel-cobalt hydrotalcite carbon composite with high specific surface area and high magnetic properties as a carrier and loading polyethyleneimine, the powdering and escape of solid amine adsorbents is solved, and high-efficiency CO2 adsorption separation and stability are achieved. In industrial applications.

CN119259004APending Publication Date: 2025-01-07CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566816.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing solid amine adsorbents are easy to powder and escape in practical applications, which are difficult to meet long-term industrial applications, and lack efficient CO2 adsorption and separation capabilities.

Method used

Magnetic porous nickel-cobalt hydrotalcite carbonaceous composite material is used as a carrier to prepare a solid amine adsorbent with high specific surface area and high magnetic properties through pyrolysis, hydroxide, reduction and mechanochemistry, and load polyethyleneimine to form efficient CO2 adsorption agent.

Benefits of technology

High-efficiency CO2 adsorption and separation are achieved, and the adsorbent has good adsorption ability to low-concentration CO2. Due to the recyclability of magnetic materials, the loss of adsorbent is significantly reduced, and it has the characteristics of high stability and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259004A_ABST
    Figure CN119259004A_ABST
Patent Text Reader

Abstract

The invention provides a magnetic solid amine CO2 adsorbent as well as a preparation method and application thereof. The adsorbent comprises an organic amine loaded magnetic porous nickel / cobalt hydrotalcite / carbon composite material. The preparation method of the adsorbent comprises the following steps: dissolving zinc nitrate / cobalt nitrate and dimethylimidazole in methanol, reacting at room temperature for 24 hours, filtering, washing and drying to obtain a product A; heating the product A at a certain temperature and atmosphere to obtain a product B; carrying out mechanochemical reaction on the product B, nickel salt, a reducing agent and the like to obtain a carrier C; the carrier C is further loaded with polyethyleneimine to prepare the solid amine CO2 adsorbent. The prepared CO2 adsorption material has the characteristics of strong magnetism, high adsorption capacity, good cycle stability and the like, can effectively prevent the problems of adsorbent loss and environmental pollution caused by adsorbent escape, and is suitable for high-efficiency adsorption and capture of low-concentration CO2 generated in the industrial fields of chemical industry, petroleum, steel and cement and the fields of power generation and traffic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carbon dioxide adsorption and capture, and specifically relates to a magnetic solid amine CO2 adsorbent and a preparation method and application thereof. Background Art

[0002] The "greenhouse effect" has become a major environmental problem facing mankind. The "greenhouse effect" is mainly caused by the excessive burning of coal, oil and natural gas in modern industrial society, which emits a large amount of tail gas. After these fuels are burned, a large amount of carbon dioxide gas is released into the atmosphere. In the long run, improving energy efficiency, saving energy and reducing emissions, adjusting the energy structure, vigorously developing renewable energy, wind energy, hydropower and nuclear energy, and increasing carbon dioxide capture and storage (CCS), the effective combination of multiple strategies is a necessary guarantee for carbon dioxide emission reduction. However, in the short term, the capture, storage and resource utilization of carbon dioxide will become the most effective and reliable choice to mitigate the "greenhouse effect". CO2 capture technologies include solvent absorption, adsorption, oxygen-enriched combustion, membrane separation, etc. Among them, the adsorption method has lower operating costs than solvent absorption and oxygen-enriched combustion, and has higher technical maturity than membrane separation and chemical chain combustion. Therefore, the capture of carbon dioxide by adsorption is a carbon capture technology with broad application prospects, and the key is the development of high-performance adsorbents.

[0003] Solid amine adsorbents are made by combining carriers with organic amines. Currently, a variety of porous materials, such as mesoporous molecular sieves, silica gel, and porous carbon materials, have been studied as carriers to load organic amines to prepare solid amine adsorbents. However, in actual applications, due to the wear of the adsorbent, the erosion of the adsorbent particles by compressed gas or fluidizing gas, etc., the adsorbent is pulverized and escapes, making it difficult to meet long-term industrial applications. The use of magnetic materials as carriers, due to their strong magnetism, makes it very easy to recover the adsorbent material, thereby greatly reducing the problem of adsorbent loss. Summary of the invention

[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a magnetic solid amine CO2 adsorbent in view of the shortcomings of the prior art. The adsorbent material prepared by the method has a good adsorption and separation ability for low-concentration CO2, and due to its strong magnetism, it is very easy to recover the adsorbent material, thereby greatly reducing the problem of adsorbent loss.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a magnetic solid amine CO2 adsorbent, comprising the following steps:

[0006] Step 1, dissolving zinc nitrate, cobalt nitrate and dimethylimidazole in a certain mass ratio in methanol, reacting at room temperature for 24 hours, filtering, washing and drying to obtain product A;

[0007] Step 2, heating the product A obtained in step 1 in a mixture of nitrogen and hydrogen to obtain product B;

[0008] Step 3, subjecting the product B obtained by the treatment in step 2 to a mechanochemical reaction with a nickel salt and a reducing agent at room temperature to obtain a carrier C;

[0009] Step 4, loading polyethyleneimine PEI on the carrier C obtained by the treatment in step 3 at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0010] In step 1, the mass ratio of the zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:1:8:200 to 1:5:12:400.

[0011] In step 2, in the nitrogen and hydrogen mixture, the volume ratio of nitrogen to hydrogen is 15:1 to 9:1, the flow rate is 20 to 40 mL / min, the heating temperature is 900° C. to 1100° C., and the heating time is 2 to 3 hours.

[0012] In step 3, the nickel salt is nickel nitrate, nickel chloride or nickel sulfate, and the reducing agent is a mixture of potassium borohydride and ethanol or a mixture of sodium borohydride and ethanol.

[0013] In step 3, when the reducing agent is a mixture of potassium borohydride and ethanol, the ratio of product B to nickel salt, potassium borohydride, and ethanol is: 120 g: 1 mol: 50 mol: 1 L to 200 g: 1 mol: 80 mol: 2 L;

[0014] When the reducing agent is a mixture of sodium borohydride and ethanol, the ratio of product B to nickel salt, sodium borohydride and ethanol is: 120g:1mol:50mol:1L-200g:1mol:80mol:2L.

[0015] In step 3, the mechanochemical reaction is to mix all the raw materials and grind them mechanically for 3 to 5 hours at room temperature.

[0016] In step 4, the amount of the loaded polyethyleneimine PEI is: the mass percentage of polyethyleneimine to the magnetic solid amine CO2 adsorbent is 30% to 40%.

[0017] The present invention also provides a magnetic solid amine CO2 adsorbent, wherein the CO2 adsorbent is prepared by the method and is a magnetic porous nickel-cobalt hydrotalcite carbon composite material supported by an organic amine.

[0018] The specific surface area of ​​the magnetic porous nickel-cobalt hydrotalcite-carbon composite material is 400 to 600 m 2 / g, and the saturation magnetization is 40~60emu / g.

[0019] The present invention also provides an application of a magnetic solid amine CO2 adsorbent, comprising: the adsorbent is loaded into a fixed bed or fluidized bed adsorption device and applied to the adsorption and capture of low-concentration CO2 generated in the chemical, petroleum, steel, cement industries, as well as power generation and transportation fields.

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses relatively common, easily available and inexpensive materials as raw materials, and obtains a carrier material with a high specific surface area and high magnetism by means of pyrolysis, hydrogenation, reduction, mechanochemical method and the like, so that the carrier is suitable for loading PEI, thereby obtaining a solid amine adsorbent with a high adsorption capacity, high CO2 regeneration stability and high magnetism, thereby being able to be used for efficient CO2 adsorption and separation; (2) The surface area of ​​the adsorbent carrier of the present invention is greater than 450 m 2 / g; the adsorbent can adsorb 85mg-CO2 / g-adsorbent or more of CO2 at a concentration of 15%; (3) under variable temperature regeneration conditions, the adsorbent of the present invention can continuously adsorb / desorb for 10 times, and the adsorption amount decreases by less than 6%; (4) the material is non-toxic and harmless, can be recovered by magnetic field adsorption, is environmentally friendly, and is of great significance to the development of large-scale CO2 adsorption and separation technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0022] Figure 1 is the X-ray diffraction pattern of the product of Example 1 and Example 3;

[0023] Figure 2 is the nitrogen adsorption-desorption curve of the carrier product of Example 2;

[0024] Figure 3 is a scanning electron micrograph of the carrier product of Example 4;

[0025] Figure 4 is a magnetic force curve diagram of the carrier product of Example 5;

[0026] Figure 5 is the adsorption curve of the products of Examples 1, 4, and 6 for 15% CO2 at 75°C;

[0027] Figure 6 The results are as follows: ... DETAILED DESCRIPTION

[0028] This embodiment provides a method for preparing a magnetic solid amine CO2 adsorbent, comprising the following steps:

[0029] Step 1, dissolving zinc nitrate / cobalt nitrate and dimethylimidazole in a certain mass ratio in methanol, reacting at room temperature for 24 hours, filtering, washing and drying to obtain product A;

[0030] Step 2, heating the material A obtained in step 1 under a nitrogen / hydrogen atmosphere to obtain a product B;

[0031] Step 3, subjecting the material B obtained by the treatment in step 2 to a mechanochemical reaction with a nickel salt, a reducing agent, etc. at room temperature to obtain a carrier C;

[0032] Step 4, loading polyethyleneimine PEI on the material C obtained by the treatment in step 3 at room temperature to prepare a solid amine CO2 adsorbent.

[0033] Furthermore, in step 1, the mass ratio of the zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:1:8:200 to 1:5:12:400.

[0034] Furthermore, in step 2, in the nitrogen / hydrogen atmosphere, the nitrogen / hydrogen volume ratio is 15:1 to 9:1, the flow rate is 20 to 40 mL / min, the heating temperature is 900° C. to 1100° C., and the heating time is 2 to 3 hours.

[0035] Furthermore, in step 3, the nickel salt is nickel nitrate, nickel chloride or nickel sulfate, the reducing agent is a mixture of potassium borohydride or sodium borohydride and ethanol, and the ratio of material B to nickel salt, reducing agent potassium borohydride or sodium borohydride and ethanol is 120g:1mol:50mol:1L~200g:1mol:80mol:2L.

[0036] Furthermore, in step 3, the mechanochemical reaction is to mix all the raw materials and grind them mechanically for 3 to 5 hours at room temperature.

[0037] Furthermore, in step 4, the amount of the loaded polyethyleneimine PEI is: the mass percentage of polyethyleneimine in the adsorbent is 30% to 40%.

[0038] This embodiment also provides a magnetic solid amine CO2 adsorbent, which is prepared by the preparation method of a magnetic solid amine CO2 adsorbent, and the specific surface area of ​​the porous nickel / cobalt hydrotalcite / carbon composite material of the CO2 adsorbent carrier is 400-600m 2 / g, and the saturation magnetization is 40-60emu / g.

[0039] This embodiment also provides an application of a magnetic solid amine CO2 adsorbent. The CO2 adsorbent is prepared by the preparation method of the magnetic solid amine CO2 adsorbent. The adsorbent can be loaded into a fixed bed or fluidized bed adsorption device and can be applied to multiple fields, including the adsorption and capture of low-concentration CO2 generated in industrial fields such as chemical, petroleum, steel, cement, as well as power generation, transportation and other fields.

[0040] Example 1: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:1:8:200, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 900°C for 2 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 15:1, flow rate is 20mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel nitrate and potassium borohydride at room temperature for 3 hours to obtain a carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 120g:1mol:50mol:1L; Material C is loaded with 40% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0041] Example 2: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:5:12:400, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 1100°C for 2 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 9:1, flow rate is 40mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel nitrate and sodium borohydride at room temperature for 3 hours to obtain a carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 200g:1mol:80mol:2L; Material C is loaded with 30% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0042] Example 3: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:2:12:300, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 1000°C for 3 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 11:1, flow rate is 30mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel chloride and sodium borohydride at room temperature for 3 hours to obtain a carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 150g:1mol:70mol:2L; Material C is loaded with 40% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0043] Example 4: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:3:10:300, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 900°C for 2 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 15:1, flow rate is 20mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel sulfate and potassium borohydride at room temperature for 3 hours to obtain carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 160g:1mol:70mol:1L; Material C is loaded with 40% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0044] Example 5: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:3:10:300, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 1100°C for 2 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 12:1, flow rate is 40mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel chloride and potassium borohydride at room temperature for 3 hours to obtain carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 160g:1mol:80mol:2L; Material C is loaded with 30% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0045] Example 6: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:4:12:400, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 900°C for 3 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 14:1, flow rate is 20mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel nitrate and sodium borohydride at room temperature for 3 hours to obtain carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 180g:1mol:80mol:2L; Material C is loaded with 40% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0046] Example 7: Zinc nitrate / cobalt nitrate and dimethylimidazole are dissolved in methanol, the mass ratio of zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:5:12:300, and the reaction is carried out at room temperature for 24 hours. Product A is obtained by filtration, washing and drying; Product A is heated at 1100°C for 2 hours in a nitrogen / hydrogen atmosphere (nitrogen / hydrogen volume ratio is 15:1, flow rate is 35mL / min) to obtain product B; Product B is subjected to a mechanochemical reaction with nickel sulfate and sodium borohydride at room temperature for 3 hours to obtain carrier C, the ratio of material B to nickel salt, reducing agent and ethanol is: 180g:1mol:80mol:2L; Material C is loaded with 40% polyethyleneimine PEI at room temperature to prepare a magnetic solid amine CO2 adsorbent.

[0047] The properties of the high-stability solid amine adsorbent prepared by the present invention are as follows:

[0048] Figure 1 It is the X-ray diffraction diagram of the product of Example 1 and 3; It can be seen that there is no characteristic peak containing metallic cobalt in the diagram, indicating that the synthetic material contains cobalt.

[0049] Figure 2 The nitrogen absorption-desorption curve of the carrier product of Example 2 is shown in Figure 2. The upper curve is the desorption curve, and the lower curve is the adsorption curve. It can be seen from the figure that the nitrogen adsorption amount of the prepared composite material increases with the increase of relative pressure, and the overall adsorption amount is relatively high. The surface area calculated by the BET method is 472m 2 / g.

[0050] Figure 3 This is a scanning electron microscope image of the product of Example 4; it can be seen from the image that the adsorbent morphology is a relatively uniform accumulation of particles with a size of 1 um. Figure 3 The Chinese and English are: acceleration voltage: HV; current: curr; sensor: det; working distance: WD; magnification: mag; horizontal field width: HFW; instrument model: Apreo 2;

[0051] Figure 4 It is the hysteresis loop of the carrier product of Example 5; it can be seen from the figure that the saturation magnetization intensity of Example 5 is close to 60emu / g.

[0052] Figure 5 The adsorption curves of the products of Examples 1, 4, and 6 for 15% CO2 (residual N2) at 75 degrees are 95.2, 92.2, and 87.3 mg / g of adsorbent, respectively. The experimental conditions are: 20 mg of adsorbent added, 60 mL / min of gas flow rate, and degassing under N2 atmosphere.

[0053] Figure 6The cyclic adsorption performance of the products of Examples 3 and 7 for 15% CO2 (residual N2) at 75 degrees. The experimental conditions are: 20 mg of adsorbent added, 60 mL / min of gas flow rate, and regeneration at 120°C with pure N2 gas after each adsorption. It can be seen that the above adsorption process was repeated 10 times, and the adsorption amount of CO2 decreased by about 6%, and the performance was stable.

[0054] The present invention provides a high-stability solid amine CO2 adsorbent and a preparation method and application thereof. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a magnetic solid amine CO2 adsorbent, characterized in that: The following steps are involved: Step 1, dissolving zinc nitrate, cobalt nitrate and dimethylimidazole in a certain mass ratio in methanol, reacting at room temperature for 24 hours, filtering, washing and drying to obtain product A; Step 2, heating the product A obtained in step 1 in a mixture of nitrogen and hydrogen to obtain product B; Step 3, subjecting the product B obtained by the treatment in step 2 to a mechanochemical reaction with a nickel salt and a reducing agent at room temperature to obtain a carrier C; Step 4, loading polyethyleneimine PEI on the carrier C obtained by the treatment in step 3 at room temperature to prepare a magnetic solid amine CO2 adsorbent.

2. The method according to claim 1, characterized in that In step 1, the mass ratio of the zinc nitrate, cobalt nitrate, dimethylimidazole and methanol is 1:1:8:200 to 1:5:12:

400.

3. The method according to claim 1, characterized in that: In step 2, in the nitrogen and hydrogen mixture, the volume ratio of nitrogen to hydrogen is 15:1 to 9:1, the flow rate is 20 to 40 mL / min, the heating temperature is 900° C. to 1100° C., and the heating time is 2 to 3 hours.

4. The method according to claim 1, characterized in that: In step 3, the nickel salt is nickel nitrate, nickel chloride or nickel sulfate, and the reducing agent is a mixture of potassium borohydride and ethanol or a mixture of sodium borohydride and ethanol.

5. The method according to claim 4, characterized in that In step 3, when the reducing agent is a mixture of potassium borohydride and ethanol, the ratio of product B to nickel salt, potassium borohydride, and ethanol is: 120 g: 1 mol: 50 mol: 1 L to 200 g: 1 mol: 80 mol: 2 L; When the reducing agent is a mixture of sodium borohydride and ethanol, the ratio of product B to nickel salt, sodium borohydride and ethanol is: 120g:1mol:50mol:1L-200g:1mol:80mol:2L.

6. The method according to claim 1, characterized in that In step 3, the mechanochemical reaction is to mix all the raw materials and grind them mechanically for 3 to 5 hours at room temperature.

7. The method according to claim 1, characterized in that In step 4, the amount of the loaded polyethyleneimine PEI is: the mass percentage of polyethyleneimine to the magnetic solid amine CO2 adsorbent is 30% to 40%.

8. A magnetic solid amine CO2 adsorbent, characterized in that: The CO2 adsorbent is prepared by the method as claimed in any one of claims 1 to 7, and the CO2 adsorbent is a magnetic porous nickel-cobalt hydrotalcite carbon composite material supported by an organic amine.

9. A magnetic solid amine CO2 adsorbent according to claim 8, characterized in that: The specific surface area of ​​the magnetic porous nickel-cobalt hydrotalcite-carbon composite material is 400 to 600 m 2 / g, and the saturation magnetization is 40~60emu / g.

10. An application of a magnetic solid amine CO2 adsorbent, characterized in that: The CO2 adsorbent is prepared by the method as described in any one of claims 1 to 7. The adsorbent is loaded in a fixed bed or fluidized bed adsorption device and is used for the adsorption and capture of low-concentration CO2 generated in the chemical, petroleum, steel, cement industries, as well as power generation and transportation fields.